2017
DOI: 10.1097/bot.0000000000000858
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Reverse Total Shoulder Arthroplasty for Proximal Humeral Fractures: Primary Arthroplasty Versus Secondary Arthroplasty After Failed Proximal Humeral Locking Plate Fixation

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 30 publications
1
37
0
2
Order By: Relevance
“…2017, Sebastia-Forcada et al. 2017). There is increasing controversy over exactly what patient- and fracture-related characteristics should lead the treating surgeon to consider THA as the primary treatment for young femoral neck fractures.…”
Section: Discussionmentioning
confidence: 99%
“…2017, Sebastia-Forcada et al. 2017). There is increasing controversy over exactly what patient- and fracture-related characteristics should lead the treating surgeon to consider THA as the primary treatment for young femoral neck fractures.…”
Section: Discussionmentioning
confidence: 99%
“…ATSA is reserved for individuals having glenoid pathology with intact rotator cuff and adequate bone stock [ 2 , 3 ]. Conversely, RTSA is indicated for irreparable rotator cuff tear arthropathy, revision procedures, and even comminuted proximal humerus fractures with low bone quality [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Five studies were identified that satisfied all inclusion and exclusion criteria. 26 , 40 43 Three studies were retrospective cohorts 26 , 42 , 43 while the other two were matched case-control. 40 , 41 All studies were published between 2016–2020.…”
Section: Resultsmentioning
confidence: 99%